Toward a Gender Sensitive and Locally Rooted co‐Production Approach: Insights From Implementing Child Stunting Eradication Program in Indonesia - Sulikah Asmorowati; Violeta Schubert; Mary S. Mangai; Jusuf Irianto; Tri Yuniningsih; Saskia Intandivanty Kamalia Anggika; Wilujeng Dwi Windhiari (Public Administration Review, 2026)
ABSTRACT Co‐production is a complex and nuanced field of social action that operates at multiple levels of the policy cycle, closely interconnecting the roles, motivations, and outcomes of different social actors. But how co‐production practices are shaped by gender is often overlooked. This article highlights the complexity of co‐production practices within Indonesia's ambitious national strategy to reduce child stunting. Based on qualitative research of three local government areas implementing stunting intervention programs, we draw on the ‘Four Co(s)’ framework to explore variations across co‐commissioning, co‐design, co‐delivery, and co‐assessment. Ongoing challenges to the eradication of stunting in some areas highlight the tense intersections between early marriage, poverty and rural and technological disadvantage. But as we argue, it is also dependent on social actors, especially women, who serve as catalysts. Future research that pays closer attention to the inherently gendered expressions of co‐production is both theoretically and practically necessary.